Analisis Kesalahan dalam Menyelesaikan Soal Struktur Aljabar Berdasarkan Prosedur Newman dengan Representasi Graf Bipartite - Novandini, Carolin; Lalang, Andrian Runtius; Simamora, Indah (Griya Journal of Mathematics Education and Application, 2025)
This study aims to analyze the types of errors made by students in the Mathematics Education Study Program, taking the Algebraic Structures course, based on Newman's Theory. The research method used was descriptive qualitative research. The subjects were 30 students who obtained test scores below 60. The data analysis technique used was an interactive technique consisting of three activity flows: data reduction, data presentation, and conclusion drawing/verification. The data presentation used bipartite graphs and, where is the set of students and the set of error types, according to Newman. The results showed that the most common type of problem transformation error was found in problem number 1 (10 students), while the most common type of problem understanding error (comprehension error) was found in problem number 2 (19 students). Therefore, several follow-up actions are needed to strengthen a deeper understanding of the definitions and properties of Algebraic Structures, namely groups and rings, and the use of non-routine and varied problems.